Urinalysis as a diagnostic tool for febrile urinary tract infection in children aged 2 months - 2 years - Ayijati Khairina; Partini Pudjiastuti Trihono; Zakiudin Munasir (Indonesian Pediatric Society Publishing House, 2014)
Background Children aged 2 months to 2 years with febrile urinary tract infection (UTI) need special attention considering kidney complications, unspecified symptoms, and difficult urine sample collection. Urinalysis was the main supportive examination for UTI because of its immediate result and widespread availability. Objective To estimate urine nitrite, leukocyte esterase (LE), leucocyturia, bacteriuria, and their combinations as a diagnostic tool for febrile UTI in children aged 2 months to 2 years. Methods This is a diagnostic study held in Cipto Mangunkusumo Hospital, Tangerang General Hospital, Fatmawati Hospital, and Budhi Asih Hospital, involving 7 5 children aged 2 months to 2 years. Urine samples for urinalysis and urine culture were collected using urine collector in all subjects. Clinical pathologists who performed urine culture, did not know the results of urinalysis. Results By parallel test analyses, we found that the best diagnostic value was the combination of 3 tests (LE, leucocyturia, and bacteriuria). This combination test showed sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (LR+), and negative likelihood ratio (LR-) of 69%, 95%, 85%, 88%, 13.1, and 0.3. Conclusion The combination test of LE, leucocyturia, and bacteriuria shows high specificity, NPV, and LR+ . Therefore, the negative results of these 3 tests in combination can be used to rule out UTI.